The Intertextualist: Future Teachers, Past Pedagogy, and Dedifferentiation in Multicultural Education - Dennis, Jeremy (Journal of Interdisciplinary Studies in Education, 2018)
Multicultural education is thought to consist of five dimensions: content integration, the knowledge-construction process, prejudice reduction, equity pedagogy, and an empowering school culture and social structure. Of the five, equity pedagogy is identified as an essential element by leading scholars in the field. Can equity pedagogy alone create the powerful learning experiences needed for multicultural education? This is an important question to consider as conservatism and dedifferentiation challenge multicultural education. If dedifferentiation is a recurring feature that impacts teachers and students, then we need a pedagogy that accounts for its significance. This article explores the ways a pedagogy of intertextuality responds to dedifferentiation and extends equity pedagogy for the development of future teachers and leaders.